2013
DOI: 10.1177/0022034513480802
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Human Technology to Capture Dentists’ Decision Policies about Pain

Abstract: Healthcare professionals use race, gender, and age cues when making pain management decisions. Use of these demographic cues, therefore, is an important topic in the study of healthcare disparities. This study used virtual human (VH) technology to investigate the effects of VH patients' demographic cues on dentists' pain management decisions. Eighty-nine dentists viewed patients with different demographic cues. Analyses revealed that dentists rated pain intensity higher and were more willing to prescribe opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
18
1
Order By: Relevance
“…This finding is consistent with previous VH idiographic studies showing that pain expression is the most commonly used cue in pain management decisions. 8,18,19 However, also consistent with previous VH idiographic studies, sex, race, and age cue use were also significant, with age being the most commonly used of these demographic characteristics. 8 Although it was most common for participants to use two cues, including pain expression, our data suggest that a significant percentage of participants relied on additional patient characteristics in evaluating the VHs’ pain intensity and in making treatment decisions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is consistent with previous VH idiographic studies showing that pain expression is the most commonly used cue in pain management decisions. 8,18,19 However, also consistent with previous VH idiographic studies, sex, race, and age cue use were also significant, with age being the most commonly used of these demographic characteristics. 8 Although it was most common for participants to use two cues, including pain expression, our data suggest that a significant percentage of participants relied on additional patient characteristics in evaluating the VHs’ pain intensity and in making treatment decisions.…”
Section: Discussionsupporting
confidence: 85%
“…1,8,9,18,19 Limited focus, however, has been placed on whether individuals are aware of their use of cues, or how these individuals would respond to feedback about their potential use of cues in making judgments about another person’s pain. The current study used an experimental approach, VH technology, and LENS model analyses, to measure participants’ use of demographic cues in pain assessment and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative feature confers a higher level of experimental control and realism than is possible with typical approaches (e.g., retrospective chart reviews, paper-pencil vignettes). We successfully used, standardized, and validated these patient stimuli in previous studies, and previous participants have rated the stimuli as highly realistic and reflective of actual clinical situations [3336,58,59]. …”
Section: Methodsmentioning
confidence: 99%
“…Additional research has consistently shown that patient demographic characteristics such as sex, race, and age may influence the pain assessment and treatment decisions of health care trainees and professionals 814. Virtual human (VH) technology has been used to demonstrate that females are perceived as experiencing higher pain intensity8,9,12–15 and are more likely to be recommended medical treatment8,9,1214 compared to males with the same clinical diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual human (VH) technology has been used to demonstrate that females are perceived as experiencing higher pain intensity8,9,12–15 and are more likely to be recommended medical treatment8,9,1214 compared to males with the same clinical diagnoses. Furthermore, African American and older adult patients are considered to have greater pain and are recommended for medical management of their pain at a higher frequency than Caucasians and younger adults, respectively 8,9,12,13.…”
Section: Introductionmentioning
confidence: 99%